2003
DOI: 10.1097/01.ogx.0000050764.67701.8c
|View full text |Cite
|
Sign up to set email alerts
|

Group B Streptococcus: Prevention of Early-Onset Neonatal Sepsis

Abstract: After completion of this article, the reader will be able to define the pathogen, describe the methods of transmission and detection, and outline the current recommendations for maternal group B streptococcus therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0
6

Year Published

2004
2004
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 49 publications
1
6
0
6
Order By: Relevance
“…When a patient is allergic to penicillin, the choices recommended by the CDC are erythromycin and clindamycin. Like other authors, we found that resistance to erythromycin and clindamycin was increasing among GBS [18], so it would be useful to test for antibiotic sensitivity, especially for penicillin-allergic women. Due to antibiotic abuse in the past, there has been an increase in resistant strains of microorganisms, which causes great concern about the restriction of antibiotics.…”
Section: Discussionsupporting
confidence: 80%
“…When a patient is allergic to penicillin, the choices recommended by the CDC are erythromycin and clindamycin. Like other authors, we found that resistance to erythromycin and clindamycin was increasing among GBS [18], so it would be useful to test for antibiotic sensitivity, especially for penicillin-allergic women. Due to antibiotic abuse in the past, there has been an increase in resistant strains of microorganisms, which causes great concern about the restriction of antibiotics.…”
Section: Discussionsupporting
confidence: 80%
“…[21][22][23][24][25][26] Our incidence of non-GBS organisms did not change, and intrinsically resistant species such as enterococcus and enterobacteria species did not increase either. There was no increased incidence of infection from penicillin-resistant bacteria; nor any loss of GBS sensitivity to penicillin.…”
Section: Discussionmentioning
confidence: 66%
“…GBS infection was first reported in 1938 1 . By 1970, it had increased dramatically and became the leading cause of neonatal death and an important cause of maternal infection.…”
Section: Discussionmentioning
confidence: 99%